Preparation method and application of membrane electrode for preparing synthesis gas through electrolyte-free CO2 electroreduction
By using membrane electrodes combining transition metal catalyst and polymer film in ultrapure water without electrolytes, the problems of carbonate deposition and electrolyte corrosion in CO2 electrolytic devices are solved, and efficient CO2 electroreduction and sustainable development are achieved .
Patent Information
- Application Number
- CN202411333474.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
Smart Images

Figure CN119121285A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of chemical technology and materials, and specifically relates to a membrane electrode for electroreduction of CO2 without electrolyte to produce synthesis gas, and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of industry, the total amount of carbon dioxide emitted into the atmosphere by humans has been rising year by year. As a greenhouse gas, carbon dioxide has brought severe challenges to the global climate. The electroreduction of carbon dioxide into high-value-added fuels or chemicals is a feasible way to achieve carbon neutrality. CO2 electrolysis technology with the production of synthesis gas as the target product has attracted much attention from researchers due to its economic development prospects and the potential for easy engineering scale-up.
[0003] Electrocatalytic CO2 reduction (CRR) is expected to achieve sustainable CO2 elimination and carbon-containing fuel production at room temperature and pressure. CRR converts CO2 into C1 products such as carbon monoxide, formic acid, methane, methanol, and multi-carbon (C2+) products with higher added value such as ethylene, acetylene, ethanol, acetic acid, propanol, etc. by obtaining 2-12 electrons.
[0004] The invention patent application with the publication number CN117430819A discloses a method for preparing a metal organic framework material for electro-reduction of CO2 to ethanol, which belongs to the technical field of catalysts for carbon dioxide reduction. The present invention uses an in-situ self-assembly method using alkaline vapor thermal diffusion and copper foam as a copper source to synthesize copper MOFs materials, whose morphology is a needle-like morphology that cannot be prepared by the existing synthesis method, and the catalyst is evenly attached to the surface of the copper foam and has a micron-sized size, which is conducive to increasing the surface area required for catalysis. The invention patent application is simple to operate, and the catalyst obtained has a uniform morphology and has a specific ethanol selectivity for electro-catalytic reduction of CO2 at a lower overpotential. The catalyst obtained by the invention patent has a smaller resistance, a higher selectivity, and a lower overpotential in catalytic CO2 reduction, so that it can reduce carbon dioxide to ethanol products under the condition of potassium bicarbonate as an electrolyte and at a voltage lower than -0.4V vsRHE, and the selectivity of carbon products is 100%.
[0005] The invention patent application with the publication number CN116065182A discloses a method for preparing a carbon-supported transition metal single atom material. The material is a transition metal single atom anchored fluorine and nitrogen co-doped carbon nanosheet electrocatalyst (M-CNF SACs), which has a two-dimensional porous nanosheet structure, wherein the nickel single atom anchored fluorine and nitrogen co-doped porous carbon nanosheet (Ni-CNF SACs) is used for electrocatalytic carbon dioxide reduction reaction (CO2RR), and has the characteristics of high catalytic activity, high selectivity and excellent stability. The device includes an anode electrode sheet, a cathode electrode sheet, a cation exchange membrane, an anode chamber electrolyte and a cathode electrolyte; the cathode catalyst is Ni-CNF SACs coated on carbon paper, and the cathode electrolyte is a CO2-saturated potassium bicarbonate solution; the anode catalyst is a three-dimensional porous cobalt diselenide catalyst (CoSe2 / CC) grown in situ on carbon cloth, and the anode electrolyte is an alkaline solution containing glycerol.
[0006] The above two invention patent applications make it easy for potassium ions to attach to the active sites when reducing CO2, so there is still room for further improvement in catalytic performance.
[0007] Currently, most small-scale or pilot-scale devices for producing synthesis gas by CO2 electrolysis are carried out in alkaline membrane electrode systems. Studies have found that there is a serious carbonate deposition problem in this system, and the alkaline electrolyte is consumed during the electrolysis process and needs to be continuously replenished. The corrosion of the alkaline electrolyte to the equipment is also not conducive to further engineering expansion. Summary of the invention
[0008] The present invention provides a method for preparing a membrane electrode for electroreducing CO2 to produce synthesis gas without electrolyte. The membrane electrode prepared by the preparation method can electroreducing CO2 efficiently in an ultrapure water electrolyte without electrolyte.
[0009] The present invention provides a method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte, comprising:
[0010] The transition metal salt, the hydroxyl-rich carbon material and the nitrogen-rich material are uniformly mixed to obtain an atomically dispersed transition metal catalyst;
[0011] Adding the transition metal catalyst to an electrode slurry dispersant to obtain a mixed slurry, and spraying the mixed slurry on carbon paper to obtain a gas diffusion electrode;
[0012] A polymer film is placed on a gas diffusion electrode and then hot-pressed to obtain a composite material, and the composite material is bonded to a proton exchange membrane to obtain a membrane electrode.
[0013] During the electrolysis of an ultrapure water electrolyte without an electrolyte, a large amount of hydrogen protons will be generated, which will easily cause a hydrogen evolution reaction and cause great interference to the CO2 reduction process. The present invention adds a polymer film between the gas diffusion electrode and the proton exchange membrane, and reduces the propagation speed of hydrogen through the polymer film, thereby reducing the hydrogen evolution reaction and correspondingly enhancing the CO2 hydrogenation reaction.
[0014] At the same time, the present invention uses transition metals with strong adsorption capacity for CO2 as active sites, thereby being able to achieve a relatively ideal catalytic reaction in an ultrapure water electrolyte.
[0015] Preferably, the transition metal is one or more of Ni, Fe, Co, Cu and Zn.
[0016] Preferably, the mass / volume ratio of the transition metal catalyst to the electrode slurry dispersant is 5-50 mg / mL.
[0017] Atomic-level distributed transition metal catalysts can enhance the effect of reducing CO2. The transition metal loading is preferably 1-20wt%. Too high a loading can easily lead to metal agglomeration and reduce the CO2 catalytic performance.
[0018] Preferably, the polymer film is a cellulose film, a polyamide film, a polyvinylidene fluoride film, a polytetrafluoroethylene film or a polypropylene film. Further preferably, the polymer film is a polyethylene film. The polymer material has a porous physical structure, which can regulate the microenvironment of the catalyst surface, and synergize with the catalyst to enhance the adsorption of CO2 and its intermediates, thereby inhibiting the hydrogen evolution reaction.
[0019] Preferably, the thickness of the polymer film is 0.1 mm-1 mm. Appropriate thickness can better control the propagation speed of proton hydrogen, avoid the mass transfer limitation caused by too thick thickness, affect the current density, and the proton penetration rate is increased due to too thin thickness, and lose the effect of inhibiting the hydrogen evolution reaction. Further preferably, when the thickness of the polymer film is 0.2 mm, the proton channel provided by the polymer film effectively balances the number of hydrogen ions required to supplement the CO2 electroreduction reaction and the number of hydrogen ions used for the hydrogen evolution reaction.
[0020] Preferably, the transition metal catalyst is a single atom catalyst, a single atom catalyst coupled with a homogeneous metal particle catalyst, a single atom catalyst coupled with a heterogeneous metal catalyst, a diatomic catalyst or a triatomic catalyst.
[0021] Further preferably, the transition metal catalyst is a Ni-based single atom coupled Ni metal particle catalyst. Ni particles regulate the electron cloud density of Ni single atoms, enhance their adsorption capacity for CO2 and its reaction intermediates, and make the electrocatalytic reaction more conducive to CO2 electroreduction.
[0022] Preferably, the hydroxyl-rich carbon material is carbon quantum dots, carbon nanosheets, carbon nanotubes or three-dimensional porous carbon material.
[0023] Further preferably, the hydroxyl-rich carbon material is carbon quantum dots.
[0024] Preferably, the nitrogen-rich material is urea, dicyandiamide, melamine or thiourea.
[0025] Further preferably, the nitrogen-rich material is urea. The urea contains oxygen elements, and the atomic-level metal catalyst with nitrogen and oxygen co-coordinated has enhanced CO2 adsorption capacity.
[0026] Preferably, the concentration of the transition metal salt is 3-100 mg / ml.
[0027] Preferably, the mass ratio of the transition metal salt, the hydroxyl-rich carbon material and the nitrogen-rich material is 1:10:15.
[0028] Preferably, the electrode slurry dispersant comprises an organic solvent, deionized water and a cation exchange resin solution;
[0029] The organic solvent is isopropanol or ethanol;
[0030] The cation exchange resin solution is a Nafion membrane solution.
[0031] More preferably, the organic solvent is isopropanol.
[0032] Preferably, the ratio of the organic solution to water is 1:1-10:1, more preferably 7:2.
[0033] Preferably, the ratio of the cation exchange resin to water is 1:1-10:1, more preferably 1:2.
[0034] Preferably, the carbon paper is 36BB carbon paper or 28BC carbon paper.
[0035] Preferably, the proton exchange membrane is a perfluorosulfonic acid membrane or a non-fluorinated sulfonic acid membrane, a polybenzimidazole (PBI) / H3PO4 membrane and a composite material proton exchange membrane.
[0036] Further preferably, the proton exchange membrane is Nafion117.
[0037] Preferably, the temperature of the hot pressing molding is 60-90°C and the pressure is 0.1-20MPa. Further preferably, the temperature of the hot pressing molding is 60°C and the pressure is 5MPa.
[0038] On the other hand, the present invention also provides an application of a membrane electrode prepared by the method for preparing a membrane electrode for electrochemical reduction of CO2 to produce synthesis gas without electrolyte in an electrocatalytic carbon dioxide reduction reaction, comprising:
[0039] The membrane electrode prepared by the preparation method of the membrane electrode for electroreduction of CO2 to synthesis gas without electrolyte and the counter electrode (iridium-plated titanium mesh) are assembled into a reaction device for reducing CO2. The electrolyte is ultrapure water, and CO2 at 10-150sccm is input into the membrane electrode.
[0040] Preferably, in order to reduce the overall cell pressure and efficiently catalyze the oxygen evolution reaction of ultrapure water, the cationic membrane electrode is titanium felt or titanium mesh, or one of titanium felt or titanium mesh coated with iridium film, preferably iridium-coated titanium mesh.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention provides a membrane electrode assembly method, including a gas diffusion electrode, a polymer film and a proton exchange membrane, which is formed into an integrated electrode by hot pressing. The electrode is easy to prepare, has excellent repeatability, and has the potential for industrial scale-up. The addition of the polymer film helps to improve the stability of the three-phase mass transfer interface, while suppressing the proton concentration in the electrode Helmholtz layer, effectively suppressing the hydrogen evolution side reaction.
[0043] The electrocatalytic reaction system assembled using the membrane electrode can efficiently convert CO2 to produce CO under the condition of using ultrapure water as the reaction medium. Operation under this condition can effectively solve the problem of electrolyte corrosion to the equipment, and at the same time solve the problem of electrolyte wet chemical pollution, which is conducive to sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram of the structure of a membrane electrode provided in a specific embodiment of the present invention;
[0045] Figure 2 TEM and STEM images of the Ni-based single-atom catalyst provided in Example 1, Figure 2 (a) is the TEM image, Figure 2 (b) is the STEM image;
[0046] Figure 3 The CO2RR performance diagram of the membrane electrode prepared in Examples 1-3, wherein Figure 3 (a) is a Faraday efficiency diagram of carbon monoxide of the membrane electrode prepared in Examples 1-3, Figure 3 (b) is a current density diagram of the membrane electrode prepared in Examples 1-3;
[0047] Figure 4 The CO2RR performance diagram of the membrane electrode prepared in Examples 4-6 and Comparative Examples 1-2, wherein Figure 4(a) is a carbon monoxide Faraday efficiency diagram of the membrane electrodes prepared in Examples 4-6 and Comparative Examples 1-2, Figure 4 (b) is a current density diagram of the membrane electrodes prepared in Examples 4-6 and Comparative Examples 1-2;
[0048] Figure 5 The CO2RR performance diagram of the membrane electrode prepared in Example 7-8, wherein Figure 5 (a) is a Faraday efficiency diagram of carbon monoxide of the membrane electrode prepared in Examples 7-8, Figure 5 (b) is a current density diagram of the membrane electrode prepared in Examples 7-8;
[0049] Figure 6 The CO2RR performance diagram of the membrane electrode prepared in Examples 9-10 and Comparative Example 3, wherein Figure 6 (a) is a carbon monoxide Faraday efficiency diagram of the membrane electrode prepared in Examples 9-10 and Comparative Example 3, Figure 6 (b) is a current density diagram of the membrane electrodes prepared in Examples 9-10 and Comparative Example 3. DETAILED DESCRIPTION
[0050] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0051] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0052] The present invention proposes a membrane electrode preparation process for CO2 electroreduction to produce synthesis gas under ultrapure water conditions, which avoids salt deposition and achieves the purpose of electrolyte cleaning, and is conducive to the sustainable development of CO2 electrolysis technology.
[0053] Example 1
[0054] Carbon quantum dots were used as precursors and urea was doped at a mass ratio of 1:10 to synthesize carbon nanosheets rich in nitrogen defects. Carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method, such as Figure 2 (a) and Figure 2 As shown in (b), under TEM, carbon quantum dots can be seen to self-assemble into wrinkled carbon nanosheets, and under STEM, evenly distributed and large numbers of Ni particles can be seen.
[0055] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0056] 10 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry dispersant and sprayed on 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0057] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.2 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the gas diffusion electrode and polyethylene film composite material was taken out and the composite material was attached tightly to the counter electrode (iridium-plated titanium mesh) to obtain a membrane electrode.
[0058] The membrane electrode prepared in this embodiment is Figure 1 As shown, a gas diffusion electrode, a polymer film and a proton exchange membrane are sequentially formed on a metal electrode plate, CO2 gas is input through the metal electrode plate, and a CO / CO2 mixed gas is output from the metal electrode plate after reduction.
[0059] The membrane electrode prepared in this embodiment was assembled into a reaction device with a cationic membrane electrode. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0060] Example 2
[0061] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0062] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0063] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry dispersant and sprayed on 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0064] The gas diffusion electrode was aligned with a polyethylene film having a thickness of 0.2 mm and placed in a hot press. The working conditions of the hot press were 5 MPa and 60°C. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was attached tightly to a Nafion 117 cation exchange membrane to assemble a cation membrane electrode.
[0065] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0066] Example 3
[0067] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0068] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0069] 30 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry dispersant and sprayed onto 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0070] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.2 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was tightly attached to the Nafion 117 cation exchange membrane to obtain a membrane electrode.
[0071] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0072] Performance Analysis:
[0073] like Figure 3 As shown in (a), the amount of catalyst sprayed on the carbon paper has a significant effect on the catalytic performance. When the catalyst loading is preferably 20 mg, the reaction selectivity is the highest; Figure 3 As shown in (b), the effect of catalyst loading on current density is positively correlated with the effect on selectivity, so a catalyst loading of 20 mg is preferred.
[0074] Example 4
[0075] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0076] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0077] Take 20 mg of Ni single atom catalyst and disperse it in 1 ml of electrode slurry dispersant, and use a spray gun to coat it on 28BC carbon paper cut into 2*2 cm. Align the carbon paper with a 0.2 mm thick polytetrafluoroethylene film and place it in a hot press. Use 5 MPa and 60°C as the working conditions of the hot press. After hot pressing for 10 minutes, take out the polymer film and gas diffusion electrode composite material, and the composite material is tightly attached to the Nafion117 cation exchange membrane to obtain a membrane electrode.
[0078] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0079] Example 5
[0080] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0081] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0082] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry and sprayed onto 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0083] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.3 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was tightly attached to the Nafion 117 cation exchange membrane to obtain a membrane electrode.
[0084] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0085] Example 6
[0086] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0087] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0088] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry dispersant and sprayed on 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0089] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.4 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was tightly attached to the Nafion 117 cation exchange membrane to obtain a membrane electrode.
[0090] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0091] Comparative Example 1
[0092] The difference from Example 5 is that the polyethylene film is not hot pressed, and the proton exchange membrane Nafion 117 is directly attached to the gas diffusion electrode.
[0093] The membrane electrode prepared in this comparative example and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0094] Comparative Example 2
[0095] The difference compared with Example 5 is that the thickness of the polyethylene film is 1.5 mm.
[0096] The membrane electrode prepared in this comparative example and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0097] Performance Analysis:
[0098] like Figure 4 (a) and Figure 4 As shown in (b), the material and thickness of the polymer film have a significant effect on the electro-reduction performance of carbon dioxide. The materials and thicknesses provided in Examples 4 to 6 enable the prepared catalyst to have good electro-reduction performance for carbon dioxide, among which the polyethylene material has the best performance in membrane electrode applications, and the thickness of the polymer film is preferably 0.2 mm. In Comparative Example 1 in which no polymer film is used in the hot pressing process and Comparative Example 2 in which a thinner polymer film is used, the hydrogen evolution reaction competes fiercely, and the CO2 electro-reduction performance is significantly inhibited, which further illustrates the necessity of selecting a suitable polymer film under ultrapure water electrolysis conditions.
[0099] Example 7
[0100] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0101] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0102] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry and sprayed onto 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0103] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.2 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was attached tightly to the Nafion 115 cation exchange membrane to assemble the cationic membrane electrode.
[0104] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0105] Example 8
[0106] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0107] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0108] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry dispersant and sprayed on 36BB carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0109] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.2 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was tightly attached to the Nafion 117 cation exchange membrane to obtain a membrane electrode.
[0110] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0111] Performance Analysis:
[0112] like Figure 5 (a) and Figure 5 As shown in (b), examples with different Nafion membrane thicknesses and different carbon paper thicknesses were added to the test. In these examples, Nafion 117 membrane and 28BC carbon paper were preferred as key materials for assembling MEA.
[0113] Example 9
[0114] Carbon nanotubes were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni single-atom catalysts were synthesized by metal salt impregnation method.
[0115] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0116] 20 mg of Ni single atom catalyst was dispersed in 1 ml of electrode slurry and sprayed onto 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0117] The gas diffusion electrode was aligned with a polyethylene film with a thickness of 0.2 mm and placed in a hot press. 5 MPa and 60°C were used as the working conditions of the hot press. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was attached tightly to the Nafion 117 cation exchange membrane to assemble the cationic membrane electrode.
[0118] The membrane electrode prepared in this embodiment and the counter electrode (iridium-plated titanium mesh) were assembled into a reaction device. The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0119] Example 10
[0120] Carbon quantum dots were used as precursors and doped with urea at a mass ratio of 1:10 to synthesize nitrogen-defective carbon nanosheets, and carbon-based Ni / Co diatomic catalysts were synthesized by metal salt impregnation method.
[0121] Isopropanol, water and Nafion membrane solution were uniformly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0122] 20 mg of Ni / Co diatomic catalyst was dispersed in 1 ml of electrode slurry and spray-coated on 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0123] The gas diffusion electrode was aligned with a polyethylene film having a thickness of 0.2 mm and placed in a hot press. The working conditions of the hot press were 5 MPa and 60°C. After hot pressing for 10 minutes, the polymer film and gas diffusion electrode composite material was taken out and the composite material was attached tightly to a Nafion 117 cation exchange membrane to assemble a cation membrane electrode.
[0124] The membrane electrode prepared in this example was assembled into a reaction device with a cationic membrane electrode (Nafion 117 membrane). The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0125] Comparative Example 3
[0126] Commercial silver powder catalyst (particle size 100 nm) was mixed with carbon powder in a mass ratio of 1:1. Isopropyl alcohol, water and Nafion membrane solution were evenly mixed in a volume ratio of 7:2:1 to prepare an electrode slurry dispersant.
[0127] 20 mg of Ag / C catalyst was dispersed in 1 ml of electrode slurry and sprayed on 28BC carbon paper cut into 2*2 cm to obtain a gas diffusion electrode.
[0128] Align the gas diffusion electrode with the polyethylene film (0.2 mm) and place it in a hot press. Use 5 MPa and 60 ° C as the working conditions of the hot press. After hot pressing for 10 minutes, take out the polymer film and gas diffusion electrode composite material. Put it close to the Nafion 117 cation exchange membrane, assemble the cation membrane electrode, and test the CO2RR performance at 30 sccm under normal pressure.
[0129] The membrane electrode prepared in this comparative example was assembled into a reaction device with a cationic membrane electrode (Nafion 117 membrane). The electrolyte of the reaction device was ultrapure water. CO2 was input into the membrane electrode at 30 sccm under normal pressure to test the CO2RR performance.
[0130] Performance Analysis:
[0131] like Figure 6 (a) with Figure 6 As shown in (b), transition metal-based catalysts synthesized using different carbon materials can achieve efficient carbon dioxide conversion in ultrapure water systems, which proves the universality of the method described in this patent in the field of using carbon-based transition metal materials for CO2 electroreduction to CO. Comparative Example 3 shows that the hydrogen evolution reaction of precious metal block materials is intense under the application method of the present invention, which is not conducive to CO2 electroreduction under ultrapure water conditions.
Claims
1. A method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte, characterized in that: include: The transition metal salt, the hydroxyl-rich carbon material and the nitrogen-rich material are uniformly mixed to obtain an atomically dispersed transition metal catalyst; Adding the transition metal catalyst to an electrode slurry dispersant to obtain a mixed slurry, and spraying the mixed slurry on carbon paper to obtain a gas diffusion electrode; A polymer film is placed on a gas diffusion electrode and then hot-pressed to obtain a composite material, and the composite material is bonded to a proton exchange membrane to obtain a membrane electrode.
2. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The transition metal is one or more of Ni, Fe, Co, Cu and Zn.
3. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The mass / volume ratio of the transition metal catalyst to the electrode slurry dispersant is 5-50 mg / mL.
4. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The polymer film is a cellulose film, a polyamide film, a polyvinylidene fluoride film, a polytetrafluoroethylene film or a polypropylene film.
5. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The thickness of the polymer film is 0.1 mm-1 mm.
6. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The hydroxyl-rich carbon material is carbon quantum dots, carbon nanosheets, carbon nanotubes or three-dimensional porous carbon material.
7. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The nitrogen-rich material is urea, dicyandiamide, melamine or thiourea.
8. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The electrode slurry dispersant includes an organic solvent, deionized water and a cation exchange resin solution; The organic solvent is isopropanol or ethanol; The cation exchange resin solution is a Nafion membrane solution.
9. The method for preparing a membrane electrode for producing synthesis gas by electroreduction of CO2 without electrolyte according to claim 1, characterized in that: The carbon paper is 36BB carbon paper or 28BC carbon paper.
10. An application of a membrane electrode prepared by the method for preparing a membrane electrode for electrochemical reduction of CO2 to produce synthesis gas without electrolyte as claimed in any one of claims 1 to 9 in an electrocatalytic carbon dioxide reduction reaction, comprising: The membrane electrode prepared by the preparation method of the membrane electrode for electroreduction of CO2 without electrolyte to produce synthesis gas is assembled with a cationic membrane electrode into a reaction device for reducing CO2, the electrolyte is ultrapure water, and CO2 at a temperature of 10-150sccm is input into the membrane electrode.
Citation Information
Patent Citations
Preparation method of carbon-supported transition metal monatomic material and electrolysis device
CN116065182A
Preparation method of metal organic framework material for electroreduction of CO2 to ethanol
CN117430819A
Cited By
Cylindrical electro-catalysis CO2 reduction reactor
CN121951569A
